KAJIAN YURIDIS TERHADAP EKSPLOITASI ANAK DI DESA PANGANDARAN - Mamay Komariah; Anda Hermana (Universitas Galuh, 2018)
This research is very important to carry out research on children in Pangandaran Village based on the observation of Pangandaran Village is quite large in the exploitation of children because it is a tourist area.This research was carried out using Qualitative Descriptive Research Methods. The data collected consist of primary data and secondary data. Primary data was obtained from interview with research respondents, namely the Employees of the Social Service of Pangandaran District and Members of the Pangandaran Police Station. Only secondary data is available at the office or in Pangandaran office and other publications.Based on the research result obtained that (1) Every carrie out on children that can cause adverse problems, mental or mental health, or moral development children, in Pangandaran Village which related to Articel 13 of Law Number 35 Year 2014 on Law Number 23 of 2002 concerning Child Protection (2) Efforts made by the Government and law enforcement for its prevention by using the Child Protection Act, and Comprehensively by making efforts that affect activities that can be categorized as child exploitation with the criminal justice process in forceKeywords: Child Protection, Child Exploitation,